Microstructure response of Amosic-3 SiC/SiC composites under self-ion irradiation. Issue 3 (March 2022) - Xu, Shanshan; Zheng, Ce; Bi, Yichun; Mao, Qingping; Qin, Hailong; Qin, Yiming; Li, Xiaoqiang
Highlights: Comprehensive TEM/STEM and micro-Raman characterization were performed. Quantitative analyses were carried out on STEM-based images. The loss of carbon packets and SiC grain growth occurred simultaneously in fibers. A grain growth theory based mechanism was proposed to explain the above result. Abstract: Amosic-3 SiC/SiC composites were irradiated at 300 °C using 6 MeV Si ions to peak doses of 13 and 55 displacements per atom (dpa). The loss of amorphous carbon packets and the growth of SiC grains were simultaneously observed in Amosic-3 SiC fibers, using a combination of transmission electron microscopy (TEM) and Raman spectroscopy. A mechanism based on the grain growth theory was proposed to expound the relationship between the loss of carbon packets and the growth of SiC grains. Small and curved SiC grains can absorb surrounding carbon packets to grow themselves; at some point, these grains further grow at the expense of adjacent small SiC grains until their grain boundary became straight. TEM images were found to support the above mechanism.